Sustainable Homestead Farming for Better Food and Nutrition Security - Humaira Sadaf, Bushra; Haque, Abdul; Miajy, Abdullah; Ahmed, Sharif; Bhandari, Humnath (2024)
Bangladesh is a densely populated agricultural-based country and about 75% of people live in rural areas. The livelihoods of rural areas directly and indirectly depend on agricultural activities. Although Bangladesh has achieved food security to some extent, malnutrition is yet a great concern, especially in the rural areas. Most people in rural areas of Bangladesh rely on rice as their staple food to satisfy their hunger. In the case of taking food, they never think about the nutritional value of the food. We know the main sources of vitamins and minerals are vegetables and fruits, but the consumption rate of vegetables and fruits in rural areas is very low. Most of the farmers in rural areas are marginal and small and they have only small pieces of land for cultivation where they grow mostly rice.